Spectroscopic investigations of iron(II) and iron(III) oxalates - D'Antonio, Maria C. (2009)
In an attempt to contribute to a better characterization of FeII and FeIII oxalate complexes, an investigation of their vibrational (infrared and Raman) and 57Fe-Mössbauer spectra was performed. It is shown that the two polymorphs, α and β, of FeC2O4.2H2O cannot be accurately differentiated with any of these spectroscopic methods, demonstrating the high structural similarity of these two crystalline forms. Partially deuterated samples of β-FeC2O4·2H2O were also investigated to improve the vibrational-spectroscopic analysis. In the case of Fe2(C2O4)3·4H2O, a structural model, derived from results of combined vibrational and Mössbauer data, could be proposed. The 298 K Mössbauer spectrum for this complex is discussed in detail for the first time.